2011
DOI: 10.1111/j.1747-0080.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Using critical incident interviews to identify the mental health knowledge, skills and attitudes of entry‐level dietitians

Abstract: Aim:  This paper aims to explore new graduates' experience working with clients with mental health issues using critical incident interviews. Methods:  The qualitative research techniques were based on phenomenology. A purposive sample of 19 new graduate dietitians was drawn from a range of work settings and locations throughout Australia. Data were gathered using 30‐minute critical incident interviews. Audiotaped data were transcribed, coded to identify common themes, compared for congruence and then categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…The origins and effects of impaired dietitian-dietitian relationships are also concerning given that national dietetics associations state their need to foster member collegiality and instil cooperation among colleagues (87,88) . Demonstrating collegiality in patient and client care (89) and collaboration with others (e.g. in a healthcare team) are requisite attributes for dietitians internationally (9)(10)(11)(12)90) .…”
Section: Discussionmentioning
confidence: 99%
“…The origins and effects of impaired dietitian-dietitian relationships are also concerning given that national dietetics associations state their need to foster member collegiality and instil cooperation among colleagues (87,88) . Demonstrating collegiality in patient and client care (89) and collaboration with others (e.g. in a healthcare team) are requisite attributes for dietitians internationally (9)(10)(11)(12)90) .…”
Section: Discussionmentioning
confidence: 99%
“…In another Australian study, interviews about critical incidents with entry-level dietitians (n = 18) who worked with nutritional concerns secondary to mental health disorders identified common sentiments including frustration, failure to see results, inadequate resources, and role limitations. 24 In a 2010 quantitative study, researchers assessed knowledge, beliefs, practices, and self-efficacy of RDNs related to ED counseling through an online survey in the United States (n = 291). 25 The most common responses were related to anxiety (feeling unsure and unprepared) and the challenge of working with clients with ED.…”
mentioning
confidence: 99%
“…Postgraduate training opportunities may offer an alternate pathway to equip dietitians to meet the anticipated workforce demand within the disability sector. Similarly, the 2011 study on the mental health knowledge, skills and attitudes of entry‐level dietitians in Australia found that these emerging professionals felt underprepared to deal with the variety of mental health situations they were facing . This study concluded that new graduates require training to address mental health situations competently, leading to the development of teaching and mentoring resources.…”
Section: Discussionmentioning
confidence: 99%